Resilience of Gen-Z people with disabilities against the dark joke phenomenon: Qualitative research - Abadi, Dinda Putri; Dzikrulloh, Mohammad Hilfi Azra; Reidana, Linka Latifany Falasifa; Wahyuni, Fitri (Psychology, Evaluation, and Technology in Educational Research, 2024)
Humor or jokes have become an integral part of social life. The Gen-Z group's response to humor is strange, especially for those above 25 years old. It is often characterized by an absurd and dark sense of humor. This will certainly cause contradictions from many parties, especially for people with disabilities who feel themselves to be the butt of jokes. In responding to dark jokes, a person with a disability uses resilience to maintain their self-actualization in the community. The objectives of this study are (1) to analyze the resilience dynamics of Gen-Z people with physical disabilities towards the dark joke phenomenon. The method used in this research is qualitative research with phenomenological design. Data collection was conducted by in-depth interviews with 3 key informants and 3 supporting informants. The results of this study indicate that aspects of resilience that arise include (1) emotion regulation; (2) Reaching out; (3) Imput control of negative behavior; (4) use of dark jokes; (5) optimism and support from the surrounding environment; (6) self-adjustment; and (7) self-efficacy. People with disabilities also use coping mechanisms as a problem-solving strategy that includes emotion focused coping and problem focused coping. Through resilience and coping owned by people with disabilities, they are able to actualize themselves and accept their physical limitations.